"She herself was the ultimate rule": Arabic biographies of missionary teachers and their pupils - Booth, Marilyn (Islam and Christian-Muslim relations, 2002)
Arabic biographies of missionary teachers and their pupils found in magazines published in Cairo and Beirut voice an indigenous perspective on missionary activity by educated women and men. The feelings of the missionaries' target population reveal a tension between local histories and foreign incursions as well as between female domesticity and professional aspirations. This larger imperial discourse informed worldwide missionary agendas for women at the turn of the twentieth century; however, the individual biographies cited within the paper demonstrate the personal interaction and effects on both foreign missionary and local women within their specific context through insightful Arab sources.